Disruption of sulfur transferase complex increases bacterial intramacrophage persistence. - Huang Tang; Zuoqiang Wang; Congcong Li; Jingchen Yu; Wanqiu Huang; Tao Zhou; Chuanzhen Zhang; Bingjie Wen; Chengyue Wang; Xiaocen Zhu; Danni Wang; Jing Tao; et al. (PLoS Pathogens)
Bacterial persisters contribute significantly to clinical treatment failure and relapse. These cells could resist antibiotic treatment via transient phenotypic and gene expression alterations. We conducted a high-throughput screening of Salmonella Typhimurium transposon mutants to identify key genes for intramacrophage antibiotic persistence. The results show that a sulfur transferase complex encoded by yheM, yheL, yheN, trmU and yhhP are involved in bacterial intramacrophage antibiotic persistence. Salmonella could persist in macrophages by downregulating the expression of the sulfur transferase complex during exposure to high concentrations of antibiotics, and even in a persistent infection mouse model. Mechanistically, deletion of yheM increases reactive nitrogen species (RNS) in the exponential phase, which inhibits bacterial respiration and ATP generation. In contrast, absence of yheM promotes persister formation by elevating (p)ppGpp levels in the stationary phase. Taken together, our data demonstrate that bacteria use the sulfur transferase to coordinate intramacrophage replication and persistence for adaptation to various environmental stresses. These findings reveal the role of the sulfur transferase complex in bacterial intramacrophage persistence and provide a promising target for antibacterial infection therapy.